GROWTH PERFORMANCE OF GIANT GOURAMY (Osphronemus gouramy) IN PRE-ENLARGEMENT PHASE WITH DIFFERENT TEMPERATURE - Subhan, Rio Yusufi; Hartono, Dwi Puji (Asian Journal of Aquatic Sciences, 2022)
The growth of giant gouramy in the pre-enlargement phase is very important, so the fish can grow and develop optimally until the enlargement phase. Water temperature is one of the many factors that directly affect the growth of fish. Water temperature significantly affects the rate of egg hatching of giant gouramy and the development of larval organs. The aim of this research is to determine optimum of water temperature on the growth of giant gourami fingerlings in pre-enlargement phase on controlled tanks. This research used a completely randomized design method with four treatments and two replications. The treatments in this study were: Control (maintenance without water heater); P1 (maintenance at 30 oC); P2 (at 32oC); and P3 (at 34oC). This research was conducted for 30 days by using giant gouramy fingerlings measuring 3,11± 0,14 cm with 50 ind/tank. The results showed that giant gouramy fingerlings was cultured at 32oC experience an absolute length growth of 5.29±0.21 cm, a daily growth rate of 3.32±0.07% and a survival rate of 94±2.82%. This indicates that the maintenance water temperature of 32oC is able to provide optimal growth for giant gouramy fingerlings in the pre-enlargement phase.